Cross sectional study to assess behavioral problems in multi-transfused thalassemic children and psychosocial factors affecting them - Kumar, Naresh; Singh, Jaspal; Khullar, Hira; Arora, Munish (International Journal of Contemporary Pediatrics, 2018)
Background: Beta‑thalassemia major is a chronic disorder of blood, having an extensive impact on the quality of life of the affected child and parents/caregivers. It involves lifelong management, with repeated blood transfusions and chelation therapy. With improved life expectancy owing to better medical facilities and education status of caregivers, psychosocial aspects of thalassemia are gaining importance. Objective of the present study was to assess the behavioral problems in multi‑transfused thalassaemic children and psychosocial factors affecting them. Methods: The study was conducted in a tertiary care level hospital having separate thalassemia day care centre. The study was a cross‑sectional study involving 100 multi‑transfused thalassaemic children of age 6-18years.Child Behavior Check List (Achenbach) (CBCL) was used to collect data from each parent regarding the child’s behavior. Parental Attitude Scale (Rangaswamy 1989) was applied. Descriptive statistical analysis was used with analysis of variance (ANOVA) and Student’s t test to find the significance of data. Results: The CBCL total scores were high in 39% patients which indicated that behavior problems are more common in thllasemic patients. Higher CBCL scores were found in older children, those having poor school performance, with mothers who are illiterate, had history of death of thalassemic relative in family, longer duration of diagnosed illness, poor pre‑transfusion hemoglobin level, and poor school attendance. Conclusions: Behavioral problems are common in multi‑transfused thalassaemic children. Timely diagnosis and appropriate remedial intervention of behavioral problems in these children would improve quality of life of these children.